Analysis of the Concept of Sharia Service Quality on Customer Decisions in Traditional Markets: (Implementation of Sharia Service in Enhancing Customer Satisfaction) - Ambar Kusuma; A. Rasikhu Z. Haramain (Student Scientific Creativity Journal, 2026)
This study examines the importance of Sharia-based service quality in traditional markets as a strategic response to the growing challenges posed by modern retail formats and digital commerce. Observed realities indicate that customers frequently experience dissatisfaction due to service practices that lack transparency and consistency. Employing a field research methodology, this study assesses how the CARTER dimensions (Compliance, Assurance, Reliability, Tangibles, Empathy, and Responsiveness) are applied within everyday muamalah interactions. The findings demonstrate that customer satisfaction in traditional market settings extends beyond rational considerations, encompassing emotional and spiritual dimensions rooted in the value of ihsan and the sense of inner peace that comes from engaging in gharar-free transactions. As a path forward, this research contends that the consistent integration of Sharia values into market practices must be positioned as a unique competitive advantage for traditional markets. Achieving this requires enhancing Islamic economic literacy among traders and reforming relevant regulations to build a sustainable and spiritually blessed Sharia retail ecosystem.